Microalgae as sources of biofuel production through waste water treatment - Muhammad Usman Akhtar; Abid Ali Khan; Wajeeha Jahangir Khan; Tiyyaba Furqan (Novel Research in Microbiology Journal)
The shortage of fuel in the near future and the change in climate due to greenhouse gases are serious challenges of a global concern, thus it is imperious to explore new sustainable ways to overwhelm these challenges. The need of a new sustainable energy sources has increased the importance of the third generation biofuel produced from non-food stocks such as algae, which possibly represent a great opportunity in the long term. The major challenge of the algae based bio-fuel production is their extraordinary cultivation costs, which make their commercialization economically infeasible. Algal spp. especially Chlorella spp. are capable of thriving in waste water and can accumulate high lipid contents. The aim of the current review was to highlight the possible integration of waste water treatment and algae based bio-fuel production, as a sustainable option for cost effective bio-fuel production along with lower environmental impact.